Application of an aesthetic evaluation model to data entry screens - Ngo, D (2001)
A screen often has to present information clearly and also act as the locus for interacting with the system. This is a complex area, involving some psychological understanding, as well as aspects of graphical design. Although knowledge of the users' tasks and abilities is the key to designing effective screen displays, an objective, automatable metric of screen design is an essential aid. In this paper, we describe a new model for quantitatively assessing screen formats. The results of applying the model to data entry screens support the use of the model. We also describe a critiquing mechanism embedded in a user interface design environment as a demonstration of our approach. (C) 2001 Elsevier Science Ltd. Ail rights reserved.